Circular polarization reconfigurable antenna for mid-band 5G applications with a new reconfigurable technique - Alaa Imran AL-Muttairi; Malik Jasim Farhan (Institute of Advanced Engineering and Science, 2020)
In this paper, a novel low cost, single-feed, and circular polarization reconfigurable antenna is designed and fabricated for future mid-band 5G applications. An innovative technique is used in this approach, which combines three techniques, namely: polygon U-slot, switchable vertical or horizontal slots, and shorting posts. The proposed antenna can alter its polarization sense between RHCP and LHCP with the ability to adjust the axial ratio position with respect to frequency along the impedance bandwidth of the antenna. The antenna is built on RT/duroid 5880 substrate with a maximum size of (31*31*3.15) .Two real diodes are integrated across the slot to change polarization sense. CST commercial software is used to simulate the antenna, and then it is fabricated and measured practically. Good agreements between the two results are achieved. However, The antenna has impedance bandwidth starting from 3.4995GHz to 3.73GHz with overlapped axial ratio bandwidth of 2.1% for both operation senses. Also, the antenna has good gain, and it has one resonant frequency at 3.6GHz for both operating states.